The function `f(x) = e^x*sin (2x)` .

The first derivative of f(x) can be determined using the product rule.

`f'(x) = (e^x)'*sin (2x) + e^x*(sin (2x))'`

= `e^x*sin (2x) + e^x*2*cos(2x)`

`f''(x) = e^x*sin (2x) + e^x*2*cos(2x) + e^x*2*cos(2x) - 2*2*e^x*sin(2x)`

= `4*e^x*cos(2x) - 3*e^x*sin(2x)`

The sum `f''(x) - f'(x) + f(x)`

= `4*e^x*cos(2x) - 3*e^x*sin(2x) - e^x*sin (2x) - e^x*2*cos(2x) + e^x*sin (2x)`

= `2*e^x*cos(2x) - 3*e^x*sin(2x)`

**For the function `f(x) = e^x*sin (2x)` , **`f''(x) - f'(x) + f(x) = 2*e^x*cos(2x) - 3*e^x*sin(2x)`